2010
DOI: 10.3233/jad-2010-1403
|View full text |Cite
|
Sign up to set email alerts
|

What Knock-Out Animals Tell Us About the Effects of Caffeine

Abstract: Abstract.Caffeine is well known for its complex pharmacological actions, in part reflecting the multiple molecular targets of caffeine. The adenosine receptors are the primary extracellular targets of caffeine. Since caffeine has similar affinity for several adenosine receptors, it has been difficult to determine which receptor subtypes mediate caffeine's effects using pharmacological tools. The development of genetic mutant mice deficient in adenosine receptors and other signaling molecules has allowed target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…It is assumed that at the concentrations typically consumed by humans caffeine acts as CNS stimulant mainly by acting as a competitive antagonist of A 1 and A 2A adenosine receptors (Fredholm et al 1999; Chen et al 2010). Here, we propose an additional complementary mechanism that may explain the effects of caffeine in a cellular and molecular model of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that at the concentrations typically consumed by humans caffeine acts as CNS stimulant mainly by acting as a competitive antagonist of A 1 and A 2A adenosine receptors (Fredholm et al 1999; Chen et al 2010). Here, we propose an additional complementary mechanism that may explain the effects of caffeine in a cellular and molecular model of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, at the concentration typically consumed by humans, caffeine may act mainly by inhibiting adenosine receptors in the CNS (Fredholm 1995). By functioning as a competitive antagonist at A 1 and A 2A adenosine receptors, it leads to diminished endogenous adenosinergic tone (Fredholm et al 1999; Chen et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Psychostimulantinduced augmentation of dopaminergic activity causes hyperlocomotion in rodents, a quantifiable response that is widely used experimentally to study susceptibility to psychotic symptoms (41 (10,43,44), adenosine is expected to exert a regulatory influence on amphetamine-induced psychomotor behavior. In line with these receptor-receptor interactions, reduced adenosinergic tone in Adk-tg mice is expected to exert a stimulatory influence on dopamine receptors, which is also considered the primary mechanism underlying the motorstimulant effect of the mixed A 1 R/A 2A R antagonist caffeine (45). Consistent with this interpretation, Adk-tg mice were hyperactive in a novel environment (25) and showed impaired LI (Figure 2), a widely established model of schizophrenia closely linked to striatal hyperdopaminergia (46).…”
Section: Adk-tg Mice -An Effective Mouse Model Of Adenosine Hypofunctmentioning
confidence: 99%
“…Genetic constitutional knockout animals for the different adenosine receptors suggest that the psychostimulant and arousal effects are mainly mediated by the A 2A adenosine receptor (11)(12)(13). However, these data cannot readily be extrapolated to the human condition because there are substantial interspecies differences with regard to the cerebral distribution and concentration of adenosine receptor subtypes.…”
mentioning
confidence: 95%